Comparative Molecular Analysis of Gastrointestinal Adenocarcinomas. - Liu, Yang; Sethi, Nilay S.; Hinoue, Toshinori; Schneider, Barbara G.; Cherniack, Andrew D.; Sanchez-Vega, Francisco; Seoane, Jose A.; Farshidfar, Farshad; Bowlby, Reanne; Islam, Mirazul; Kim, Jaegil; Chatila, Walid; et al. (Cancer Cell, 2018)
We analyzed 921 adenocarcinomas of the esophagus, stomach, colon, and rectum to examine shared and distinguishing molecular characteristics of gastrointestinal tract adenocarcinomas (GIACs). Hypermutated tumors were distinct regardless of cancer type and comprised those enriched for insertions/deletions, representing microsatellite instability cases with epigenetic silencing of MLH1 in the context of CpG island methylator phenotype, plus tumors with elevated single-nucleotide variants associated with mutations in POLE. Tumors with chromosomal instability were diverse, with gastroesophageal adenocarcinomas harboring fragmented genomes associated with genomic doubling and distinct mutational signatures. We identified a group of tumors in the colon and rectum lacking hypermutation and aneuploidy termed genome stable and enriched in DNA hypermethylation and mutations in KRAS, SOX9, and PCBP1.
EVALuna2:35936